External Trade of Transport Services in a Developing Economy: Status and Progress Prospects - NABIEV, Erboz N.; BAZAROVA, Saulegul K.; AKBAYEV, Erbolsyn T.; RAIHANOVA, Gulnur A.; DARIBEKOV, Serik S. (Journal of Advanced Research in Law and Economics, 2017)
The state transport is a tool for the solution of a wide range of social, economic and defense tasks. The world experience shows that the harmonious development of different types of transport and a clear organization of their interaction makes transport a single complex, which provides services for the implementation of the carriage of goods and passengers, is the activity of the economic entity, aimed at changing the location of people or lots of cargo, and carried out with prior approval of the manufacturer services and customer. For developing States such as Kazakhstan, which are located far away from main shopping centers, the development of transit services is an important component of economic development. This article analyses the foreign trade transport services on the basis of the following indicators: exports and imports of services for cargo transportation by types of transport, analysis of transport services export in terms of transportation and types of transport, the volume of cargo in international traffic by type of transport. Despite the lack of direct access to the sea, in Kazakhstan is quite developed transit services. However, there are a number of problems such as high cost of transportation and irregular load transport routes. In connection with these difficulties, proposed the main ways of development of transit policy of Kazakhstan. The results of this article can be used to improve transport logistics transit States.